2007
DOI: 10.1111/j.1365-2966.2007.11930.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of trans-Neptunian binaries through chaos-assisted capture

Abstract: The recent discovery of binary objects in the Kuiper-belt opens an invaluable window into past and present conditions in the trans-Neptunian part of the Solar System. For example, knowledge of how these objects formed can be used to impose constraints on planetary formation theories. We have recently proposed a binary-object formation model based on the notion of chaos-assisted capture. Here we present a more detailed analysis with calculations performed in the spatial (three-dimensional) three- and four-body … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 143 publications
(379 reference statements)
2
55
0
Order By: Relevance
“…However, the majority of Kuiper Belt binaries consist of comparable mass companions with wide separations and have too much angular momenta to have formed by the same mechanism. Instead these systems most likely have a dynamical origin like, for example, binary formation by threebody capture, or binary formation aided by dynamical friction (Weidenschilling 2002;Goldreich et al 2002;Funato et al 2004;Astakhov et al 2005;Lee et al 2007). The Hill sphere, the region interior to an object's Hill radius, sets the maximum phase space available for binary formation by such dynamical processes.…”
Section: Implications For Kuiper Belt Binariesmentioning
confidence: 99%
“…However, the majority of Kuiper Belt binaries consist of comparable mass companions with wide separations and have too much angular momenta to have formed by the same mechanism. Instead these systems most likely have a dynamical origin like, for example, binary formation by threebody capture, or binary formation aided by dynamical friction (Weidenschilling 2002;Goldreich et al 2002;Funato et al 2004;Astakhov et al 2005;Lee et al 2007). The Hill sphere, the region interior to an object's Hill radius, sets the maximum phase space available for binary formation by such dynamical processes.…”
Section: Implications For Kuiper Belt Binariesmentioning
confidence: 99%
“…In order to find evidence for specific formation scenarios of BMPs, it is therefore essential to take the Kozai evolution of the BMPs into account. For example, typical high-eccentricity BMPs produced in some scenarios such as the expected e > 0.8 in the exchange scenario of Funato et al (2004), or 0.2 e 0.8 in the chaos assisted capture scenario (Lee et al 2007), could be observed with very low eccentricities, either due to the random phase in which they are observed during their Kozai cycle or due to their KCTF evolution which would have circularized their orbit (e.g., Figure 2). Recently, (and after the initial presentation of this manuscript), Petit et al (2008) have reported on the peculiar orbit of the Kuiper Belt binary 2001 QW 322 , with very large SMA but relatively small eccentricity.…”
Section: Kctf Observational Signature and Bmps Formations Scenariomentioning
confidence: 99%
“…However, the majority of observed binary KBOs are roughly equal-mass, wide-separation binaries (Noll et al 2008b) that have too much angular momentum to be formed by the same mechanism. Motivated by this challenge, a series of new binary formation scenarios was proposed (e.g., Weidenschilling 2002;Goldreich et al 2002;Funato et al 2004;Astakhov et al 2005;Lee et al 2007;Nesvorný et al 2010). Most of these scenarios appeal to interactions within the Hill sphere, the region interior to the Hill radius of a KBO.…”
Section: Binary Formation Scenariosmentioning
confidence: 99%